The paradigm of harmony in the confucian tradition - Costantini, Filippo (2016)
Harmony is one of the most important concepts of the Confucian tradition. Along Confucianism, harmony represented most of the time the ultimate ideal that man needs to pursue. Confucians employed the concept and paradigm of harmony in several fields from politics to ethical, aesthetics and so on. Hence it can be said that harmony is one of the most comprehensive concept within the Confucian tradition, and without a proper understanding of it, it is not possible to entirely grasp the essence of Confucianism. This essay aims to analyze and define the concept and the paradigm of harmony within the Confucian tradition. First, I will deal directly with the term, showing the roots and the development of the concept from pre-imperial China to Han dynasty. Second, I will define the general paradigm of harmony: harmony depicts the ongoing triadic process of polarity interaction that implies dynamicity, creativity and comprehensiveness as necessary elements.